Pulsatilla patens (Ranunculaceae), a perennial herb, is ectomycorrhizal in northeastern Poland and likely shares ectomycorrhizal fungi with Pinus sylvestris - Jason Hoeksema; Mélanie Roy; Grazyna Łaska; Aneta Sienkiewicz; Amber Horning; Matthew J. Abbott; Claire Tran; Joshua Mattox (Acta Societatis Botanicorum Poloniae, 2018)
The sharing of species of ectomycorrhizal fungi (EMF) among different co-occurring host plant species could allow the formation of common mycorrhizal networks, which can alter plant–plant interactions and succession. Such sharing of EMF among woody species is thought to be common in many forests, but very few herbaceous plants form EMF, so they are assumed to be excluded from EMF networks in forests. We studied the EMF on roots of a common coniferous tree, Pinus sylvestris, and a co-occurring rare herbaceous perennial plant, Pulsatilla patens (Ranunculaceae), in northeastern Poland. We examined roots from co-occuring P. sylvestris and P. patens, visually classified EMF into morphotypes, studied tissue sections of mycorrhizal structures using compound microscopy, and used DNA sequencing to identify the fungi. On both host plant species, we observed EMF colonization, with colonized root tips exhibiting a swollen appearance, as well as a variety of colors and textures of fungal mycelium covering and emanating from those swollen tips. Sectioning and microscopic examination of an EMF morphotype common on P. patens confirmed the presence of a mantle and Hartig net, indicating the likely presence of functional ectomycorrhizal structures. The two most frequent EMF were Cenococcum geophilum and Piloderma olivaceum, and the latter was found to associate with both host plant species. Several EMF found here only on P. patens, including C. geophilum and two Russula species, are known from previous studies to also associate with P. sylvestris and other tree species. The observation of shared EMF between a coniferous tree and an understory herb indicates the potential for common mycorrhizal networks to alter interactions between these two species and may also indicate a unique way in which the distribution and abundance of a rare herbaceous plant may be influenced by shared mutualisms with a common co-occurring woody plant.